Uncovering Atomic‐Scale Stability and Reactivity in Engineered Zinc Oxide Electrocatalysts for Controllable Syngas Production. Issue 28 (10th June 2020) - Daiyan, Rahman; Lovell, Emma Catherine; Huang, Bosi; Zubair, Muhammad; Leverett, Joshua; Zhang, Qingran; Lim, Sean; Horlyck, Jonathan; Tang, Jianbo; Lu, Xunyu; Kalantar‐Zadeh, Kourosh; Hart, Judy N.; et al.
Abstract: In this study, scalable, flame spray synthesis is utilized to develop defective ZnO nanomaterials for the concurrent generation of H2 and CO during electrochemical CO2 reduction reactions (CO2 RR). The designed ZnO achieves an H2 /CO ratio of ≈1 with a large current density ( j ) of 40 mA cm −2 during long‐term continuous reaction at a cell voltage of 2.6 V. Through in situ atomic pair distribution function analysis, the remarkable stability of these ZnO structures is explored, addressing the knowledge gap in understanding the dynamics of oxide catalysts during CO2 RR. Through optimization of synthesis conditions, ZnO facets are modulated which are shown to affect reaction selectivity, in agreement with theoretical calculations. These findings and insights on synthetic manipulation of active sites in defective metal‐oxides can be used as guidelines to develop active catalysts for syngas production for renewable power‐to‐X to generate a range of fuels and chemicals. Abstract : Defective ZnO is reported to generate syngas with a H2 /CO ratio of ≈1 and a current density of 40 mA cm −2 during continuous CO2 reduction reactions (CO2 RR) at a cell voltage of 2.6 V. Through in situ atomic pair distribution function analysis, the remarkable stability of these ZnO structures, is explored, addressing the knowledge gap in understanding the dynamics of oxide catalysts during CO2 RR.